Validity and reliability of the Greek translation of the Job Satisfaction Survey (JSS) - Tsounis, Andreas; Sarafis, Pavlos (My University, 2018)
Background: Job satisfaction is fundamental to employee well-being and successful operation of an organization. The use of effective tools for assessing it is imperative for management research. Our main purpose was to translate and adapt the Job Satisfaction Survey (JSS) questionnaire to the Greek language and to test its psychometric properties. Methods: The tool was translated into Greek and then back into English by different bilingual translators. The Greek JSS was tested with a sample of 239 employees of various specialties in drug addiction treatment. Confirmatory Factor Analysis (CFA) for validity testing as well as internal consistency analysis for reliability testing was conducted. Results: The results confirmed that: (a) the translated version is an accurate translation of the original, (b) CFA results indicated that the nine-factor structure model was a great choice; the factor loads were high and ranged from 0.61 to 0.90, and (c) the reliability coefficients were satisfactory (Cronbach’s alpha for eight of the nine dimensions of the Greek JSS scale ranged from 0.62 to 0.87 except for the dimension “Operating procedures” which was 0.48, while Cronbach’s alpha for the total scale was 0.87 and the Gutman Split-Half Coefficient was 0.88). Conclusions: The findings suggested that the Greek Version of JSS is a valid and reliable tool for measuring job satisfaction in Greece. Further research for assessing its psychometric values in various samples and further analysis for studying its validity and testing its internal and external consistency and coherence might be conducted in the future.
Keywords: Job satisfaction; JSS questionnaire; Reliability